WABAH PENYAKIT MENULAR (COVID 19) DAN PERUMPAMAAN DALAM AL-QURAN - Hestina, Niken Ayu (Institut PTIQ Jakarta, 2020)
One of the words frequently expressed by the Koran is that of disaster. When examining the Koran, the word calamity itself comes from the root word Asaba along with its derivation, which is found quite often, which is 77 times mentioned. In the Koran itself also contains many signs and prohibitions that are useful for humanity. Specifically the word disaster itself is mentioned 10 times in the Koran. Therefore, as a creature of God who is endowed with reason, it should be our duty to reveal what is in the Koran. Disasters are no exception according to Qadla and Qadar Allah. And to overcome the calamity include: to believe in the fate of Allah SWT. Be sure if there will be a wisdom that is taken behind each of these calamities, and we should always introspect ourselves. Quraish Shihab in Tafsir al - Misbah, the nature of disaster is sunatullah in testing every human being and is a hidden blessing from Allah.